826 NEW THERAPEUTIC PERSPECTIVES IN CARDIAC AMYLOIDOSIS. (15th December 2022) - Giovannetti, Alessandro; Accietto, Antonella; Caponetti, Angelo Giuseppe; Saturi, Giulia; Ponziani, Alberto; Massa, Paolo; Sguazzotti, Maurizio; Gagliardi, Christian; Galiè, Nazzareno; Biagini, Elena; Longhi, Simone
Abstract: Man, 72 years old, smoker, hypertensive and dyslipidemic, came to our clinic suspected of heart disease with a hypertrophic phenotype. In anamnesis there was a recent hospitalization for heart failure in the course of undated atrial fibrillation. During hospitalization because of the presence of antero-septal and lateral QS complexes, a coronary disease was excluded by coronary angiography while the echocardiogram showed a left ventricle with moderate concentric wall thickening, LVEF 38% with a restrictive transmitral pattern. The patient was discharged on therapy with ramipril, bisoprolol, canrenone, furosemide and rivaroxaban with an electrical cardioversion program which had been subsequently ineffective. At the time of the first evaluation the patient was symptomatic of dyspnea in functional class NYHA III, he also reported in anamnesis a progressive reduction of exercise tolerance for about two years and a previous surgery for bilateral carpal tunnel syndrome 5 years earlier. The echocardiogram showed concentric parietal thickening in the presence of granular sparkling, apical sparing, thickening of the valvular apparatus and reduced GLS (- 12%) which led to a suspect of cardiac amyloidosis. To complete the diagnosis, the patient underwent: total-body bone scan with 99-Tc-DPD (Perugini score = 2); assay of serum kappa and lambda light chains (negative), serum and urinary immunofixation (negative), NT-proBNP (980 pg / mL) and a determination of troponin I (32 ng / L) which showed a picture of transthyretin cardiac amyloidosis. The genetic sampling confirmed the presence of the Ile68Leu transthyretin mutation and a neurological evaluation with electromyography ruled out a peripheral polyneuropathy. During follow-up the patient presented a worsening of clinical and instrumental pattern despite the progressive uptitration of diuretic therapy and the addition of metolazone with a simultaneous deterioration of left ventricular dysfunction (LVEF 30%) at echocardiogram. Therefore, the patient's case and possible therapeutic strategies were discussed collectively as it was not possible to access conventional therapies for cardiac amyloidosis with Tafamidis, Inotersen and Patisiran due to the contextual functional class NYHA> II and the absence of polyneuropathy, not it was possible to undertake biventricular resynchronization in the absence of intraventricular block or to implement therapy for heart failure with reduced ejection fraction due to intolerance. As a last option, implantation of a cardiac contractility modulation device (CCM) was proposed and performed via right subclavicular. At the successive follow-up after implantation, the patient showed a slight clinical and instrumental improvement and it was possible to reduce the diuretic dose, discontinuing metolazone. The echocardiogram also showed a slight increase in LVEF (35%). The long-term outpatient evaluation of the patient is currently underway with the aim of undertaking specific therapy with Tafamidis if the prescription criteria are met. Family screening has started. Conclusion: the present clinical case represents an example of the application of alternative and potentially effective therapeutic strategies in patients with cardiac amyloidosis not susceptible to conventional pharmacological treatments.